THE CONFERENCE OF THE PARTIES: A FUTURE FOR A MORE PROFOUND MULTILATERALISM IN TAX MATTERS? - Živkovic, Lidija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The present contribution is aimed at assessing the potential practical reach of the Conference of the Parties, a mechanism provided for under art. 31 of the Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting, which was signed on 7 June 2017 in Paris and to which currently 94 taxing jurisdictions are signatories. Since the scope of application of the Conference of the Parties is conditioned on the legal nature and modus operandi of the said Convention, the first part of the article will be dedicated to their analysis. Furthermore, the author will consider in detail the provisions of the Convention intended to establish the procedural framework for the operation of the Conference of the Parties. The analysis will then be focused on some of the essential questions which the Convention failed to regulate: the decision-making process applicable by the Conference of the Parties and the legal effect of its future decisions, by having recourse to the Vienna Convention on the Law of Treaties. Although it remains questionable if the Conference of the Parties could have a role as important as it does in other fields of public international law, considering the countries’ traditionally vigilant approach to the limitations of their fiscal sovereignty, the author contends that this mechanism could potentially serve as a basis for a more thorough cooperation between taxing jurisdictions worldwide, especially now that the world is struggling with yet another economic crisis. What seems to be necessary in this respect is the shift of international tax policy design from a handful of richest countries to a more inclusive circle of jurisdictions, for which the Conference of the Parties could provide a framework.